Estudo da assimetria da fossa mandibular, em crânios secos de crianças pelo método radiográfico - Rocha, João Carlos da [UNESP] (Universidade Estadual Paulista (Unesp), 1999)
The Temporomandibular Joint is a noble structure of the complex mandibular, a lot of research was conducted on the to signs and symptoms of the alterations that attack those structures. ln spite of the high incidence of the DTM in children, there's little knowledge about it, wich makes difficult the treatment Desorders Craniomandibulares (DCM) or Desorders Temporomandibulars (DTM). The Temporomandibular Joint is composed basically by three elements: bones, muscles and disk, in relation to bony part, we have the fossae mandibular that is part of the temporary bone and wich houses the condyle mandibular, accomplishing the articulation among the cranium and the jaw (it leaves piece of furniture of the articulation). Our intention in that work was of verifying a possible asymmetry of the fossae mandibular on the left side and of the right side in relation to two straight line: a straight line that coincided with the plane medium sagittal and another perpendicular straight line to the plan medium sagittal. Analyzing, the fossae mandibular in 91 dry craniums of children, with age varying between four months of life intrauterina and five years, in x-rays in that the incidence was cranium-flow, we could end that: in spite of we find statistical significance in relation to that asymmetry, clinic cannot affirm that interferences on occlusion exists for that asymmetry

A Articulação Temporomandibular é uma estrutura nobre do complexo maxilomandibular, muito se tem estudado em relação a sinais e sintomas das alterações que acometem essas estruturas. Apesar disso, pouca atenção foi dada a essa estrutura em pacientes jovens, por isso pouco conhecimento existe sobre quais crianças necessitam de tratamento, apesar da alta incidência de Desarranjos Craniomandibulares (DCM) ou Desarranjos Temporomandibulares (DTM). A Articulação Temporomandibular é composta basicamente por três elementos: ossos, músculos e disco, em relação a parte óssea, temos a fossa mandibular que faz parte do osso temporal e que aloja o côndilo mandibular, realizando a articulação entre o crânio (parte fixa da articulação) e a mandíbula (parte móvel da articulação). Nossa intenção nesse trabalho foi de verificar uma possível assimetria das fossas mandibulares do lado esquerdo e do lado direito em relação a duas retas: uma reta que coincidia com o plano sagital mediano e uma outra reta perpendicular ao plano sagital mediano. Analisando, a fossa mandibular em 91 crânios secos de crianças, com idade variando entre quatro meses de vida intrauterina e cinco anos, em radiografias em que a incidência foi crânio-caudal, pudemos concluir que: apesar de encontrarmos significância estatística em relação a essa assimetria, clinicamente não podemos afirmar que existe interferências oclusais por essa assimetria
Keywords: Oclusão dentária; Odontopediatria; Cranio - Radiografia; Articulação temporomandibular; Temporomandibular Joint